Cardiovascular risk factors in people deprived of their liberty: an integrative review - Gabrielle Pessôa da Silva; Sheila Coelho Ramalho Vasconcelos Morais; Cecília Maria Farias de Queiroz Frazão; Camila Takáo Lopes; Suzana de Oliveira Mangueira; Francisca Márcia Pereira Linhares (Universidade Federal do Rio Grande do Sul, 2020)
ABSTRACT Objective: To investigate the scientific evidence on the most frequent risk factors for cardiovascular disease in persons deprived of their liberty. Methods: An integrative literature review carried out in the CINAHL, Medline/Pubmed, Scopus, LILACS, CUIDEN, Web of Science and Virtual Health Library portal databases using the following keywords: cardiovascular diseases, risk factors, prisons, prisoners. Results: The final sample consisted of 17 primary articles published in English and Spanish. Overweight and obesity were the most cited cardiovascular risk factors besides diabetes, hypertension, smoking, dyslipidemia, consumption of alcohol and other drugs, physical inactivity, metabolic syndrome, anxiety, depression and unhealthy heart diet. Conclusions: The most frequent risk factors for cardiovascular disease in persons deprived of their liberty were those classified as modifiable. In the prison setting, these factors are enhanced due to an environment with little modification of these opportunities.